Research Weaving: Visualizing the Future of Research Synthesis. (March 2019) - Nakagawa, Shinichi; Samarasinghe, Gihan; Haddaway, Neal R.; Westgate, Martin J.; O'Dea, Rose E.; Noble, Daniel W.A.; Lagisz, Malgorzata
Abstract : We propose a new framework for research synthesis of both evidence and influence, named research weaving. It summarizes and visualizes information content, history, and networks among a collection of documents on any given topic. Research weaving achieves this feat by combining the power of two methods: systematic mapping and bibliometrics. Systematic mapping provides a snapshot of the current state of knowledge, identifying areas needing more research attention and those ready for full synthesis. Bibliometrics enables researchers to see how pieces of evidence are connected, revealing the structure and development of a field. We explain how researchers can use some or all of these tools to gain a deeper, more nuanced understanding of the scientific literature. Highlights: An exponential increase in scientific publications requires informative and integrative reviews to provide a detailed synthesis of a particular research field, and this has resulted in the emergence of novel methods for synthesizing heterogeneous research. Research weaving provides a novel framework that combines bibliometrics and systematic mapping to inform the development of a field, the influence of research papers and their interconnections, and to visualize content across and within publications. Research weaving has the potential to provide a more efficient, in-depth, and broad synthesis of a research field, to identify research biases, gaps, and limitations. Such insights have the potential to inform ecological and environmental policy and communicate research findings to the general public in more effective ways then are typically done in current research syntheses.